2007
DOI: 10.1037/0096-1523.33.6.1335
|View full text |Cite
|
Sign up to set email alerts
|

The role of spatial and nonspatial information in visual selection.

Abstract: Even though it is undisputed that prior information regarding the location of a target affects visual selection, the issue of whether information regarding nonspatial features, such as color and shape, has similar effects has been a matter of debate since the early 1980s. In the study described in this article, measures derived from signal detection theory were used to show that perceptual sensitivity is affected by a top-down set for spatial information but not by a top-down set for nonspatial information. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
95
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 73 publications
(113 citation statements)
references
References 120 publications
(213 reference statements)
10
95
8
Order By: Relevance
“…Although tactile cuing produced efficient search for some spatial frequencies, the results of Experiment 3 demonstrated that visual cues produced more efficient search slopes than did tactile cues. This may have occurred because the visual cue provided a more accurate or more detailed representation of the target or may have been a result of visual priming (Theeuwes, Reimann, & Mortier, 2006;Theeuwes & Van der Burg, 2007;.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although tactile cuing produced efficient search for some spatial frequencies, the results of Experiment 3 demonstrated that visual cues produced more efficient search slopes than did tactile cues. This may have occurred because the visual cue provided a more accurate or more detailed representation of the target or may have been a result of visual priming (Theeuwes, Reimann, & Mortier, 2006;Theeuwes & Van der Burg, 2007;.…”
Section: Discussionmentioning
confidence: 99%
“…In this experiment, prior to the search display, participants were presented with the Gabor that would appear in the target ring as a cue. Previous studies have shown that this improved visual selection in a visual search task when using a color cue (Theeuwes & Van der Burg, 2007. Participants completed the tactile cue condition from Experiment 2 as a comparison with the visual cue condition.…”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…Evidence for the former stems from studies in which the amount of information available about the target identity in singleton search tasks was manipulated (Egeth, 1977;Meeter & Theeuwes, 2006;Müller, Heller, & Ziegler, 1995;Müller, Reimann, & Krummenacher, 2003;Theeuwes & Van der Burg, 2007;Treisman, 1988). A typical finding is that search is faster when observers know the identity of the target dimension within a block of trials than when the target dimension changes from trial to trial; this is referred to as a cross-dimensional cost.…”
mentioning
confidence: 99%